Numerical study on conjugate heat transfer characteristics of liquid lead-bismuth eutectic and supercritical carbon dioxide in a PCHE straight channel. (15th June 2023) - Su, Xing-Kang; Li, Xian-Wen; Wang, Xiang-Yang; Chen, Qi-Jian; Shi, Qian-Wan; Qiu, Jing; Gu, Long
Highlights: A two-equation model is used to reproduce the LBE-cooled flow and the Reynolds analogy hypothesis is applied to predict the heat transfer of S-CO2 far from the pseudo-critical region. The inlet Reynolds number of S-CO2 is identified as the main factor affecting heat transfer. The effects of inlet flow rates and inlet temperature on the detailed thermal–hydraulic behavior of a PCHE straight channel are quantitatively analyzed. The relevant research results of this paper can provide a reference for optimizing CFD conjugate heat transfer model between LBE and S-CO2 . Abstract: The Printed Circuit Heat Exchanger (PCHE) is the optimal heat transfer structure of the fourth-generation advanced Lead–Bismuth Eutectic (LBE) cooled fast reactor coupling with the supercritical carbon dioxide (S-CO2 ) Brayton cycle system. It is of great significance to study the conjugate heat transfer characteristics between LBE with low Prandtl number turbulent heat transfer characteristics and S-CO2 with supercritical convective heat transfer characteristics. However, the conventional Reynolds analogy assumption will affect the numerical heat transfer precision of LBE and, thus, the accuracy of the coupled heat transfer of LBE and S-CO2 . In the present work, an advanced two-equation turbulent heat transfer model, which can effectively correct the numerical heat transfer process of LBE, is introduced into the conjugate heat transfer solver of the open-source Computational Fluid Dynamics (CFD) program OpenFOAM, where the Reynolds analogy assumption is retained to reproduced the heat transfer of S-CO2 flow away from the pseudo-critical region. The currently developed model and numerical method are compared with the experimental data of an LBE-cooled pipe and the simulation data of conjugated heat transfer of S-CO2 and S-CO2 in a PCHE straight channel. The results show that the calculation method in this study can improve the numerical conjugate heat transfer accuracy of LBE compared with the Reynolds analogy assumption model and can reproduce the flow and heat transfer process of S-CO2 in a PCHE straight channel. Then, the conjugate heat transfer characteristics between LBE and S-CO2 in a PCHE straight channel are studied. The effects of inlet Reynolds number and inlet temperature are focused on to study the conjugate heat transfer law of LBE coupling S-CO2 .